1993
DOI: 10.1523/jneurosci.13-07-02829.1993
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate neurons in hypothalamus regulate excitatory transmission

Abstract: The hypothalamus is the crucial part of the brain that regulates homeostasis throughout the body. It governs the endocrine and autonomic nervous systems, temperature, heart rate, emotional and motivational states, reproduction, energy and water balances, and circadian rhythms. In contrast to the prevailing belief that hypothalamic neurons use peptides, neuromodulators, or other slow-acting agents as their principal neuroactive substances, we present data indicating that the primary excitatory transmitter relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(33 citation statements)
references
References 25 publications
0
32
0
1
Order By: Relevance
“…In light of the findings that in early development the excitatory actions of GABA can influence neurite growth and branching, synapse formation, division of neuronal progenitor cells, migration, and growth cone calcium levels (Meier et al 1984;Michler, 1990;Barbin et al 1993;LoTurco et al 1995;, our finding that NT_3 can enhance the excitatory activity of GABA suggests that NT_3 could act through GABA to influence a wide variety of developmental events. In our previous work, we found that virtually all synaptic events in hypothalamic cultures and slices could be blocked by GABA and glutamate receptor antagonists (van den Pol & Trombley, 1993;Chen et al 1996;Belousov & van den Pol, 1997). In the light of this, we think our experiments done in the presence of glutamate receptor blockers show an effect of NT_3 on developing GABAergic neurones.…”
Section: Discussionmentioning
confidence: 57%
“…In light of the findings that in early development the excitatory actions of GABA can influence neurite growth and branching, synapse formation, division of neuronal progenitor cells, migration, and growth cone calcium levels (Meier et al 1984;Michler, 1990;Barbin et al 1993;LoTurco et al 1995;, our finding that NT_3 can enhance the excitatory activity of GABA suggests that NT_3 could act through GABA to influence a wide variety of developmental events. In our previous work, we found that virtually all synaptic events in hypothalamic cultures and slices could be blocked by GABA and glutamate receptor antagonists (van den Pol & Trombley, 1993;Chen et al 1996;Belousov & van den Pol, 1997). In the light of this, we think our experiments done in the presence of glutamate receptor blockers show an effect of NT_3 on developing GABAergic neurones.…”
Section: Discussionmentioning
confidence: 57%
“…PAG expression has been used in a number of previous studies to visualize and quantify glutamate-transmitting neurons [1,[38][39][40]48,75]. Glutamate has been firmly established as the predominant excitatory transmitter in the hypothalamus [5,51,74], and it's activity has been extensively linked to aggression in a range of animal models, including rats, mice, cats, and fighting bulls [6,30,36,56,57,71,76], where it appears be positively associated with the aggressive behavioral phenotype. In preliminary studies, we have shown that PAG containing neurons in the AH express 5HT1B receptors (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…and inhibitory inputs to the cell, and terms excite E and inhibit E represent the reversal potentials for excitatory ions and inhibitory ions, respectively (Grossberg, 1973;Hodgkin and Huxley, 1953;van den Pol and Trombley, 1993;Bertrand and Changeux, 1995). Term leak g is a constant leakage conductance and leak E is the reversal potential of leaked ions.…”
Section: Appendix: Mathematical Equations and Parametersmentioning
confidence: 99%